Calibration of Raman wavenumber in large Raman images using a mercury‐argon lamp. (30th April 2020) - Jakubek, Ryan S.; Fries, Marc D.
Abstract: Raman imaging is an emerging tool for the analysis of meteorites, as it is capable of describing mineralogy, carbon composition/speciation, and crystal orientation all within a petrographic context. Adequately examining the heterogeneous composition of a meteorite often requires long image collection times on the timescale of days. However, the wavenumber calibration of the Raman spectrometer drifts over long timescales resulting in low wavenumber precision for the Raman spectra comprising a large Raman image. This decrease in wavenumber precision can compromise the analysis of geological markers that can provide important information on a meteorite sample. We examine, in detail, the change in bandwidth and wavenumber of the Raman bands and Hg–Ar emission lines in our Raman images as a function of time and laboratory temperature. To overcome the drift in calibration, we utilize a commercial WITec Raman instrument with a built‐in Hg–Ar calibration lamp to individually calibrate each spectrum in the Raman image. We show that using the Hg–Ar calibration, we can improve the wavenumber precision for the spectra in our Raman images from ±0.15 to ±0.05 cm −1 for Raman spectra collected over multiple days. This is important as it improves measurements of mineral chemistry, latent strain, and other features that are dependent upon accurate peak position determination. We also examine the spectral signal‐to‐noise ratio needed to minimize the wavenumber error when fitting bands to Gaussian/Lorentzian profiles. We then use our results to suggest a general method for calibrating the wavenumber of Raman spectra in large Raman images. Abstract : We examined the drift in Raman wavenumber calibration when collecting Raman images over long timescales. Using a mercury‐Argon lamp, we propose a method to calibrate each Raman spectrum within a Raman image to improve wavenumber precision and accuracy. Using our calibration method, we improve the precision of our observed band Raman wavenumber from ±0.15 to ±0.05 cm −1 .